Dying with dementia: most frequent symptoms. A review of the literature / Sterben mit Demenz: die häufigsten Symptome. Eine Literaturübersicht - Koppitz Andrea; Waldboth Veronika; Dreizler Jutta; Imhof Lorenz (Sciendo, 2015)
Sensing, observing and interpreting the symptoms of persons suffering from dementia is very challenging. The difficulties lie in their restricted capacity to communicate and irregular transitions from a chronic-stable to an acute-critical condition both in the course of their symptoms and in the slow but continuous process of deterioration.